Implementation of numbered head together model to increase students’ activeness and learning output in primary schools - Benny Prakoso; Elvira Hosein Radia (Universitas Pendidikan Ganesha, 2019)
The purpose of this study was to determine the increase in activeness and learning outcomes of the 4th grade students of SD Negeri Pasekan 03 Ambarawa District by applying the Numbered Head Together (NHT) model. This type of research was a classroom action research accomodating a research model by Kemmis and Mc Taggart carried out with 4 stages including planning, action, observation and reflection, which carried out 2 cycles which each cycle consisted of 3 meetings. The results of the study were obtained from class IV SD Pasekan 03 students totaling 30 students (1) in the pre-cycle learning outcomes of student learning outcomes during the learning there were 20 students who did not complete with a percentage of 33.3% and 10 completed with percentages 66.66% of students in pre-cycle learning. (2) in learning using Numbered Head Together (NHT) learning model in the first cycle of students who completed 14 students with a percentage of 46.67% and those who did not complete 16 students with a percentage of 53.33%. (3) the results of the study in the second cycle of students who completed 24 students with a percentage of 80% and those that did not complete there were 6 students with a percentage of 20%. learning outcomes theme 7 sub-theme 1 learning 1 and 2 experienced a significant increase for 4th grade students of SD Negeri Pasekan 03, students seemed active, cheerful, pleasant and also enthusiastic in the learning process.